Effect of monensin on weight gain, growth traits, and semen characteristics in yearling beef bulls - Peters, C.W.; Laudert, S.B.; Corah, L.R.; Krehbiel, C.L.; Nichols, David A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feeding the ionophore monensin to yearling beef bulls improved (P<.05) weight gain by 4.2%. Final hip height was similar between treatments, but bulls fed monensin had almost 1 cm greater (P<.01) scrotal circumference and more than 10 cm 2 larger (P<.01) pelvic area. Semen characteristics generally were unaffected by treatment. However, bulls fed monensin had less (P<.01) semen motility than controls. Approximately 30 sperm morphology traits were evaluated; values were similar between treatments except for those traits listed. Collection date tended to influence (P<.15) volume, concentration, motility, and postfreeze characteristics.
Keywords: Beef; Bulls; Performance; Monensin; Semen; Ionophore; Morphology